Analisis Kebijakan Standar Penilaian Pendidikan di Indonesia Pada Mata Pelajaran PAI - Zubaidi, Zubaidi (Journal of Industrial Engineering & Management Research, 2022)
- Evaluation is one component of the educational curriculum that is very important and cannot be separated from other curriculum components so that it becomes a system in which there are components that interact, interrelate and are interdependent with each other. So that there is equality for all students both in urban and regional areas with the standardization of assessments in order to realize the goals of national education. Equity and quality of education will make citizens have life skills so that they have the ability to recognize and overcome problems of themselves and their environment, encourage the establishment of a civil and modern society imbued with Pancasila values. This study uses qualitative research methods and the type of library research.The results of this study indicate that in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 66 of 2013 concerning Educational Assessment Standards, it is stated that what is meant by Educational Assessment Standards are criteria regarding mechanisms, procedures, and instruments for assessing student learning outcomes. The juridical basis of this Educational Assessment Standard is the National Education System Law no. 20 of 2003, Government Regulation no. 19 of 2005 concerning National Education Standards, and Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 66 of 2013 concerning Educational Assessment Standards. Assessment standards by educators according to BSNP include general standards, planning standards, implementation standards, processing and reporting standards of assessment results and standards for the use of assessment results. Each of these standards has principles and criteria set by BNSP. Meanwhile, the assessment of learning outcomes carried out by the education unit has two main standards that must be considered, namely: the standard for determining grades and the standard for determining graduation. Juridically, namely in the National Education System Law no. 20 of 2003, assessment in education is associated with quality improvement. Both the quality of students and the quality of the education unit itself. Therefore, this assessment also covers the institution, including the programs that exist within the institution itself. Moreover, the assessment of learning outcomes also involves community participation which is carried out through independent institutions whose evaluations are carried out periodically, thoroughly, transparently, and systematically to assess the achievement of national education standards. Evaluation of Islamic Religious Education (PAI) must cover three domains, namely cognitive, affective, and psychomotor. To undergo the process of the three domains, of course, the process of measuring each domain must be carried out for each student. In this evaluation, the right instrument is needed so that the results can be valid and comprehensive. Therefore, in terms of cognitive (KI 3) it can be in the form of test questions, in the affective domain (KI 1 and 2) can use portfolio instruments (such as student worship report books), student behavior notebooks. Meanwhile, in terms of psychomotor using an instrument of observation rubric which contains indicators of competence in the PAI subject. This evaluation does require cooperation between the teacher and the parents/guardians of students